The Collectio Britannica and its Sources: Reviewing the Trustworthiness of a Key Witness of Medieval Papal Letters - Rolker, Christof (Zeitschrift der Savigny-Stiftung für Rechtsgeschichte. Kanonistische Abteilung, 2022)
The Collectio Britannica, compiled in the late 11th century and preserved in only one manuscript (London, BL, Add MS 8873), contains numerous excerpts from papal letters dating from the fifth to the eleventh centuries, including many that are not known from other sources. For a long time it was considered a reliable source, but between the 1940s and 1980s some scholars expressed doubts about the authenticity of various letters found in the Britannica, and even in more recent research the collection is still viewed with suspicion. However, a re-examination of the relevant studies shows that many arguments against the authenticity of the papal letters as found in the Britannica were speculative at best. Most ‘suspicious’ elements are in fact found only in the extant London copy of the Britannica, not in the version used in the 1090s by Ivo of Chartres and his collaborators. Only in very few cases is there reason to believe that the sections of the Britannica in question contain extracts from forged or falsified papal letters. With the exception of the section on Leo IV, the relevant parts of the Britannica can usually be relied upon to faithfully retain the content, wording, cursus, and even the order of the papal registers on which they are ultimately based. Content: I. Introduction, The Extant Copy, Why Think the Britannica Draws on Registers? - II. Possible Manipulations by the Britannica Compiler, p. 121, Sancta octo and the Ecumenicity of Constantinople IV, The Britannica Interpolated by Ivo?, Kuttner’s Doubts on JL 5383 and JE 3180, Confusing Nicholas I, Hincmar, and Saint Cyprian, Summary. - III. Much Smoke but Little Fire: Supposed Forged Sources Behind the Britannica, p. 132, Leo’s pallium Grant for Hincmar, The Excommunication of the Emperor, A ‘Great Stumbling Block’: Ullmann and JE 2646, Ullmann on the Letters of Gelasius I, The ‘Archbishop of Dol’ in JE 3003, Summary. - IV. Chronological Order, p. 149, Gelasius I and Pelagius I, Alexander II, John VIII, Saint Boniface, Urban II, Leo IV (and Stephen V), Summary. - V. Selection Criteria, p. 161. - VI. Conclusions, p. 165